Observations of fin whales and vessels offshore oregon using fibre optic distributed acoustic sensing - Steve Horne; Anna L. Stork; Frantisek Stanek (Frontiers in Marine Science, 2025)
We analysed Distributed Acoustic Sensing (DAS) data from a fibre optic sensing system deployed on an existing submarine cable located offshore Oregon to characterize fin whale calls. A sequence of over 300 calls in a 2-hour period was identified using the conventional earthquake detection technique of template matching. With these initial detections we then used a robust correlation, and stacking process to estimate the call signatures and timings. Calls were found to be of two distinct types that are typical for fin whales and referred to as doublets. The calls typically alternate between the two types with an inter-call interval of approximately 15 seconds. These sequences pause approximately every 12 minutes for a couple of minutes before recommencing. These breaks are interpreted to be the whale resurfacing to breath. We track the whale’s location over two hours using conventional location methods from time picks derived from a correlation process. This shows that the whale moved eastwards, towards the Pacific coastline, before turning to the south. Coincidentally, during this time frame a large container vessel also traverses the submarine fibre optic cable. The distance between the vessel and the whale ranges between 16 km and 2km at the closest point of approach. The whale initially appears to turn north as the vessel approaches to within 10km of the vessel and then follows an erratic localized track before proceeding in a southward direction away from the vessel. This behaviour may be indicative of an avoidance behaviour. This observation suggests fibre optic acoustic measurement systems could routinely monitor underwater radiated noise from marine traffic and marine mammals using existing seafloor cables to establish typical behavioural patterns.